Crystallinity and surface morphology of the Poly Ethylene Glycol-added cholesteryl acrylate-ITO composites. Issue 6 (March 2021) - Afrizal, A; Budi, S; Ismail, M; Gracia, G; Intan, I; Bryan, B
Abstract: Composite of cholesteryl acrylate-ITO nanoparticle was synthesized with the addition of polyethylenegycol (PEG). The crystallinity and surface morphology of the composites were investigated. XRD pattern of that product showed peaks in 2θ at 21° and confirmed a nematic phase. Therefore, added PEG could be changed the structures liquid crystal of cholesteryl acrylate. Percent crystallinity of the composites with different PEG variations of 0.001, 0.002, 0.003, 0.004, and 0.005 are0.001 is 8.14%, 12.41%, 14.85%, 7.11, and 8.66%, respectively. SEM image of the composite with PEG 0, 003 indicated showed the formation of rods and chains crosslinking indicating successful photopolymerizations process. Those conditions made polymer to be micelle that affect their conductivity due to aggregation.